Cuantificación de resveratrol por hplc de vinos tintos producido por los viñeros Danielito en el distrito de Cascas provincia Gran Chimú - Pérez Gutierrez, Eduard Enrique (2012)
The purpose of this study was to quantify resveratrol in red wine by HPLC, produced in the city of Cascas, is working with the red wines of the vineyard Danielito because numerous epidemiological studies have shown that moderate wine consumption is associated with a lower incidence cardiovasculares. También disease we must to wine is attributed many beneficial health properties such as antioxidant, anticancer, antispasmodic, activating bile secretion, antibacterial and antihistamine among others. To a large extent these properties are due to the polyphenols in wine, and within this group stilbene among them the results obtained to quantify resveratrol.Los resveratrol was the average of 2.94mg / L to be of consideration according to the literature. That is why we present this research project is aimed at the population and thus contribute to meeting the needs of the population in health care.